On the Erdos-Ko-Rado property of finite groups of order a product of three primes - Modjtaba Ghorbani; Mina Rajabi-Parsa (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2019)
Let G be a subgroup of the symmetric group Sn. Then G has the Erdos-Ko-Rado (EKR) property, if the size of any intersecting subset of G is bounded above by the size of a point stabilizer of G. The aim of this paper is to investigate the EKR and the strict EKR properties of the groups of order pqr, where p, q, r are three prime numbers.